MASTERING TIME MANAGEMENT TO ACHIEVE SUCCESS - Bekkulova Hojar Zayniddinovna; Eshdavlatova Jasmina Akramjon qizi (Web of Journals Publishing, 2024)
Effective time management is the foundation of success in both personal and professional affairs. This article explores important strategies and techniques for mastering time management to achieve greater productivity, satisfaction, and fulfillment. The article emphasizes the importance of setting clear goals and priorities as a basis for effective time management. It discusses the importance of setting achievable goals and setting priorities based on their urgency and importance.
Keywords: allocating time strategically, procrastination, time management system, setting boundaries, urgency, adaptability.